Using Emergence to Take Social Innovation to Scale - Wheatley, Margaret; Frieze, Deborah (The Shambhala Institute, 2007)
In spite of current ads and slogans, the world doesn’t change one pers on at a time. It changes as networks of relationships form among peopl e who discover they share a common cause and vision of what’s possible . This is good news for those of us intent on changing the world and c reating a positive future. Rather than worry about critical mass, our work is to foster critical connections. We don’t need to convince larg e numbers of people to change; instead, we need to connect with kindre d spirits. Through these relationships, we will develop the new knowle dge, practices, courage, and commitment that lead to broad-based chang e. But networks aren’t the whole story. As networks grow and transform into active, working communities of practice, we discover how Life tr uly changes, which is through emergence. When separate, local efforts connect with each other as networks, then strengthen as communities of practice, suddenly and surprisingly a new system emerges at a greater level of scale. This system of influence possesses qualities and capa cities that were unknown in the individuals. It isn’t that they were h idden; they simply don’t exist until the system emerges. They are prop erties of the system, not the individual, but once there, individuals possess them. And the system that emerges always possesses greater pow er and influence than is possible through planned, incremental change. Emergence is how Life creates radical change and takes things to scal e. Emergence has a life-cycle. It begins with networks, shifts to inte ntional communities of practice and evolves into powerful systems capa ble of global influence. Since its inception in 1992, The Berkana Inst itute has striven to learn how living systems work, how they emerge fr om networks to communities to systems of influence. In our global work —primarily with economically poor communities in many different nation s—we have experimented actively with emergence in many different conte xts. We have demonstrated what’s possible when we connect people acros s difference and distance. By applying the lessons of living systems a nd working intentionally with emergence and its life-cycle, we have be come confident that local social innovations can be taken to scale and provide solutions to many of the world’s most intractable issues.